2020
DOI: 10.3166/pson-2020-0135
|View full text |Cite
|
Sign up to set email alerts
|

Efficacité de l’hypnose pour prendre en charge la fatigue associée au cancer : une revue de la littérature internationale

Abstract: Objectif : Les études qui s’interrogent sur l’efficacité des interventions non médicamenteuses, dans la prise en charge de la fatigue associée au cancer, comprennent le plus souvent des sessions d’activités physiques adaptées ou des prises en charge psychologiques. Parmi elles se trouve l’hypnose, mais elle est principalement proposée en combinaison avec une autre thérapie, limitant une interprétation en termes d’efficacité. À travers cette revue de la littérature, nous voulons comprendre quelle est la place d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Studies in breast cancer patients show a positive effect of hypnosis combined with CBT on symptoms of distress and physical fatigue (Cramer et al, 2015 ; Roe et al, 2016 ). A recent literature review found that only six studies investigated the effectiveness of hypnosis (not combined with another therapy) on cancer symptoms and CRF (Baussard et al, 2020 ). Results indicate that four studies reported effectiveness of hypnosis: two studies when the session is conducted by a therapist (Montgomery et al, 2007 ; Jensen et al, 2012 ), with effect sizes ( d ) equal to 0.80 and 2.05 respectively, and two studies reported significant efficacy of auto-hypnosis (listening audio-tape) (Bragard et al, 2017 ; Gregoire et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in breast cancer patients show a positive effect of hypnosis combined with CBT on symptoms of distress and physical fatigue (Cramer et al, 2015 ; Roe et al, 2016 ). A recent literature review found that only six studies investigated the effectiveness of hypnosis (not combined with another therapy) on cancer symptoms and CRF (Baussard et al, 2020 ). Results indicate that four studies reported effectiveness of hypnosis: two studies when the session is conducted by a therapist (Montgomery et al, 2007 ; Jensen et al, 2012 ), with effect sizes ( d ) equal to 0.80 and 2.05 respectively, and two studies reported significant efficacy of auto-hypnosis (listening audio-tape) (Bragard et al, 2017 ; Gregoire et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Montgomery et al ( 2007 ), a two-arm RCT with n = 100 for the hypnosis intervention seems more robust but assessed post-surgery fatigue, which again is very specific. Thus, this review of the international literature concludes that there is a lack of studies on the effectiveness of hypnosis for CRF (Baussard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%